2001
DOI: 10.1001/archinte.161.20.2406
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Testing and Medical Decision Making

Abstract: A S ILLUSTRATED in this issue of the ARCHIVES, genetic testing is an increasingly informative tool in the diagnosis, prevention, and treatment of disease. The usefulness of this tool, however, hinges on its transparency in the clinical setting. Results of research 1-7 indicate that clinicians will experience predictable difficulties in interpreting probabilities associated with genetic testing, indeed with testing generally. These difficulties can be avoided by following the guidelines herein. With respect to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 16 publications
3
37
0
Order By: Relevance
“…For example, in a study examining triage decisions for patients presenting to emergency rooms with chest pain, expert cardiologists processed information in a cruder all-or-none fashion (patients were either at risk or not at risk of an imminent heart attack) and they processed fewer dimensions of information than less expert physicians or students did (see also . Consistent with fuzzy-trace theory, the evidence suggests a shift to increasingly qualitative, simplified processing with increasing expertise in a domain (Reyna, Lloyd, & Whalen, 2001; Reyna, Lloyd, & Woodward, 1997;Shanteau, 1992). …”
mentioning
confidence: 64%
“…For example, in a study examining triage decisions for patients presenting to emergency rooms with chest pain, expert cardiologists processed information in a cruder all-or-none fashion (patients were either at risk or not at risk of an imminent heart attack) and they processed fewer dimensions of information than less expert physicians or students did (see also . Consistent with fuzzy-trace theory, the evidence suggests a shift to increasingly qualitative, simplified processing with increasing expertise in a domain (Reyna, Lloyd, & Whalen, 2001; Reyna, Lloyd, & Woodward, 1997;Shanteau, 1992). …”
mentioning
confidence: 64%
“…Understanding risks and making good decisions requires health literacy and "numeracy" (Reyna & Brainerd, 2007; 2008) to interpret the meaning of base rates, joint probabilities (Wolfe & Reyna, 2010a,b) conditional probabilities, (Peters, McCaul, Stefanek, Nelson, 2006; Wolfe, Fisher & Reyna, 2012) and other quantitative concepts. Systematic biases in risk estimation have been demonstrated for both patients and providers (Offit, 2006; Reyna, Lloyd, & Whalen, 2001; Reyna, Nelson, Han, & Dieckmann, 2009). Women must also reason with ambiguous technical information in the context of conflicting attitudes and competing goals and constraints.…”
Section: 2 Breast Cancer and Genetic Riskmentioning
confidence: 99%
“…In his seminal work, Eddy (1982) showed that various health care professionals-doctors, nurses, and midwives-have difficulties understanding, communicating, and correctly solving statistical problems. Similarly, Reyna (2001) argued that health care professionals ''experience predictable difficulties in interpreting probabilities associated with genetic testing'' (p. 2406; see also Gigerenzer, 2002). Yet this is some of the very information that the American College of Obstetricians and Gynecologists recommends that patients be given.…”
mentioning
confidence: 99%